2004
DOI: 10.1002/zaac.200400314
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structures and Properties of Na2ReO3 and of a Second Modification of Na5ReO6

Abstract: Single crystals of Na5ReO6 have been obtained from the reaction of Na2O, rhenium metal and CdO in Ag containers at 550 °C. At 700 °C Na2ReO3 is formed possibly via a topotactic redox reaction of Na5ReO6 with rhenium metal. Here we report the crystal structures of Na2ReO3 and a second modification of Na5ReO6, ex‐situ X‐ray diffraction studies of the reactivity within the system Na / Re / O, selected spectroscopic investigations of the two compounds and Extended‐Hückel calculations of the [Re2O6]4‐ anion, contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this regard, Na 2 ReO 3 was not included in the ICSD Database. However, this system was still incorporated in the present study since it was found to be synthesized . We performed full structural optimization of the stable compositions in the present analysis of the formation energies of the 3d–5d double perovskites.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Na 2 ReO 3 was not included in the ICSD Database. However, this system was still incorporated in the present study since it was found to be synthesized . We performed full structural optimization of the stable compositions in the present analysis of the formation energies of the 3d–5d double perovskites.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, this system was still incorporated in the present study since it was found to be synthesized. 76 We performed full structural optimization of the stable compositions in the present analysis of the formation energies of the 3d−5d double perovskites. The formation energy of the 3d−5d systems with reference to the minimum energy combination of stable compositions are shown in Figure 5c.…”
mentioning
confidence: 99%
“…The X-ray diffraction analysis of sodium sulfate slag at Figure 6 shows that sodium sulfate is present in two structural modifications, part of the sodium sulfate (41.4%) also undergoes structural changes during melting, and rhenium is present in two perrhenate forms, NaReO4 and Na5ReO6. Formation of perrhenates with anionic residue ReO 4-proceeds in wide temperature intervals with metal oxides, but Na5ReO6 formation requires special conditions of synthesis at the interaction of sodium oxide Na2O and metallic rhenium [22]. These data also do not exclude the formation of metallic rhenium with the subsequent formation of the compounds, Na5ReO6.…”
Section: Thermogravimetric Studiesmentioning
confidence: 95%
“…Thermogravimetric studies and the results of physical and chemical analyses of crude lead and slag, consisting mainly of sodium sulfate, demonstrate that the reduction smelting of lead slime, with a sodium sulfate consumption of 30% and a coke consumption of 5%, proceeds with the formation of crude lead due to the decomposition of lead sulfate with a subsequent reduction to metallic lead. Osmium compounds are also reduced to a metallic state and collected in the lead melt, like all platinum metals [22].…”
Section: Thermogravimetric Studiesmentioning
confidence: 99%
See 1 more Smart Citation